En tegning og en tegner - Katznelson, Ib (Rambam. Tidsskrift for jødisk kultur og forskning, 2014)
Ib Katznelson was only a little boy when, in the fall of 1943, he and his family were captured by the Germans as they were trying to escape to Sweden. Ib and his mother were taken to the concentration camp Ravensbrück and, later, ended up in another camp, Theresienstadt, where most of the captured Danish Jews were taken to. In Theresienstadt, a young Dutch girl made a drawing of him, but he forgot her name. With the help of researcher Silvia Goldbaum Tarabina Fracapane, Ib managed to find the woman in Holland, and in 2013, after almost 70 years, the two of them met again and exchanged stories. Through Ib, we are now able to hear the story about her illegal work under the German occupation of Holland, her capture and her life in the camps.